DAGESTAN INJECTION CRAFT BY METAL ON WOOD: FROM FOLK CRAFTMANSHIP TO PROFESSIONAL ART - Garunova, Saida Magomedhanovna; Saidova, Anzela Saidovna (History, Archeology and Ethnography of the Caucasus, 2020)
The article contains an analysis of the principles of decor and the peculiarity of the artistic style of ornamental notches with metal on wood - one of the most significant types of crafts in Dagestan. The sources and stages of development of this type of craft to the level of professional art are traced. On the example of the work of the national artist of the Russian Federation, Gamzat Gazimagomedov, the importance of professionalizing an art notch with metal on wood in the preservation of this type of folk art is shown. Consideration of the most significant works of G. Gazimagomeddov in the context of the traditional Untsukul ornamental notch art and decorative arts of the Russian Federation as a whole made it possible to identify the stylistic features of the compositional construction of the Avar ornamental notch art in the artist’s works, to present his artistic contribution as a treasury of the decorative and applied art of the Russian Federation and Dagestan, and in solving practical problems of preserving and developing the national x art crafts of the country.